PROBLEMATIKA PASAL 174 AYAT (2) KOMPILASI HUKUM ISLAM: TINJAUAN TERHADAP DASAR-DASAR HUKUM YANG MENDUKUNGNYA - Hasan, Abi (Universitas Muhammadiyah Ponorogo, 2022)
This discussion describes the problem of inheritance of girls who spend all of their parents' inheritance, this problem arises when the Qur'anic verse clearly states that the share of inheritance for girls if they are not accompanied by boys will only get half if they are alone, while if two or more get two-thirds. of the total inheritance. The Compilation of Islamic Law (KHI), which is the main reference for the Indonesian Religious Courts in resolving inheritance problems for Indonesian Muslims, requires daughters to spend the entire inheritance, after the share of the father, mother, husband or wife. This is generally illustrated in Article 174 paragraph (2) of the KHI, so that the existence of this article seems to be very contrary to the qath'i argument that states the inheritance share of girls. The purpose of this paper is to describe the existence of Article 174 paragraph (2) of the KHI in resolving the inheritance problems of girls in Indonesia, precisely in the Religious Courts, as well as the legal arguments that support it which are certainly in the Islamic legal order. Based on the discussions that have been carried out, it was found that the application of Article 174 paragraph (2) as intended has often occurred in the Indonesian Religious Courts, this started from the Supreme Court Decision No. 86 K/AG/1994 and No.184 K/AG/1995 which are the forerunners of every existing decision. Then the supporting arguments are also very numerous, starting from the opinion of Ibn Abbas ra, the opinion of the Shia School, the opinion of an Islamic scholar, namely Muhammad Syahrur and also Hazairin who is an expert on Islamic inheritance in Indonesia.